Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the equation [tex]\( 2 \sin^2 x = 1 - \cos x \)[/tex] on the interval [tex]\([0, 2\pi)\)[/tex], let's go through the steps meticulously.
1. Rewrite the equation using a trigonometric identity:
We know that [tex]\(\sin^2 x = 1 - \cos^2 x\)[/tex]. However, it will be helpful to use another identity to simplify our calculations. First, let's rewrite the equation as:
[tex]\[ 2 \sin^2 x + \cos x - 1 = 0. \][/tex]
2. Use the double-angle identity:
Recall that [tex]\( \sin^2 x = \frac{1 - \cos(2x)}{2} \)[/tex]. However, another useful form of transformation is using:
[tex]\[ \sin^2 x = 1 - \cos^2 x. \][/tex]
So, rewriting the expression in terms of [tex]\(\cos x\)[/tex], we have:
[tex]\[ 2(1 - \cos^2 x) + \cos x - 1 = 0. \][/tex]
Simplify this to:
[tex]\[ 2 - 2 \cos^2 x + \cos x - 1 = 0. \][/tex]
Simplify further:
[tex]\[ -2 \cos^2 x + \cos x + 1 = 0. \][/tex]
Notice this is a quadratic equation in terms of [tex]\(\cos x\)[/tex]:
[tex]\[ 2 \cos^2 x - \cos x - 1 = 0. \][/tex]
3. Solve the quadratic equation for [tex]\(\cos x\)[/tex]:
[tex]\[ 2y^2 - y - 1 = 0, \quad \text{where} \quad y = \cos x. \][/tex]
To solve for [tex]\(y\)[/tex], use the quadratic formula [tex]\(y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex]:
[tex]\[ y = \frac{-(-1) \pm \sqrt{(-1)^2 - 4(2)(-1)}}{2(2)} = \frac{1 \pm \sqrt{1 + 8}}{4} = \frac{1 \pm \sqrt{9}}{4} = \frac{1 \pm 3}{4}. \][/tex]
This gives us two solutions:
[tex]\[ y = \frac{4}{4} = 1 \quad \text{and} \quad y = \frac{-2}{4} = -\frac{1}{2}. \][/tex]
Thus, we have:
[tex]\[ \cos x = 1 \quad \text{and} \quad \cos x = -\frac{1}{2}. \][/tex]
4. Find the corresponding [tex]\(x\)[/tex]-values within the interval [tex]\([0, 2\pi)\)[/tex]:
- For [tex]\(\cos x = 1\)[/tex]:
[tex]\[ x = 0. \][/tex]
- For [tex]\(\cos x = -\frac{1}{2}\)[/tex]:
[tex]\[ x = \frac{2\pi}{3}, \quad \text{and} \quad x = \frac{4\pi}{3}. \][/tex]
5. Gather all the solutions:
Thus, the solutions to the equation [tex]\( 2 \sin^2 x = 1 - \cos x \)[/tex] on the interval [tex]\([0, 2\pi)\)[/tex] are:
[tex]\[ x = 0, \frac{2\pi}{3}, \frac{4\pi}{3}. \][/tex]
Hence, the correct answer is:
[tex]\[ \boxed{0, \frac{2\pi}{3}, \frac{4\pi}{3}}. \][/tex]
1. Rewrite the equation using a trigonometric identity:
We know that [tex]\(\sin^2 x = 1 - \cos^2 x\)[/tex]. However, it will be helpful to use another identity to simplify our calculations. First, let's rewrite the equation as:
[tex]\[ 2 \sin^2 x + \cos x - 1 = 0. \][/tex]
2. Use the double-angle identity:
Recall that [tex]\( \sin^2 x = \frac{1 - \cos(2x)}{2} \)[/tex]. However, another useful form of transformation is using:
[tex]\[ \sin^2 x = 1 - \cos^2 x. \][/tex]
So, rewriting the expression in terms of [tex]\(\cos x\)[/tex], we have:
[tex]\[ 2(1 - \cos^2 x) + \cos x - 1 = 0. \][/tex]
Simplify this to:
[tex]\[ 2 - 2 \cos^2 x + \cos x - 1 = 0. \][/tex]
Simplify further:
[tex]\[ -2 \cos^2 x + \cos x + 1 = 0. \][/tex]
Notice this is a quadratic equation in terms of [tex]\(\cos x\)[/tex]:
[tex]\[ 2 \cos^2 x - \cos x - 1 = 0. \][/tex]
3. Solve the quadratic equation for [tex]\(\cos x\)[/tex]:
[tex]\[ 2y^2 - y - 1 = 0, \quad \text{where} \quad y = \cos x. \][/tex]
To solve for [tex]\(y\)[/tex], use the quadratic formula [tex]\(y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex]:
[tex]\[ y = \frac{-(-1) \pm \sqrt{(-1)^2 - 4(2)(-1)}}{2(2)} = \frac{1 \pm \sqrt{1 + 8}}{4} = \frac{1 \pm \sqrt{9}}{4} = \frac{1 \pm 3}{4}. \][/tex]
This gives us two solutions:
[tex]\[ y = \frac{4}{4} = 1 \quad \text{and} \quad y = \frac{-2}{4} = -\frac{1}{2}. \][/tex]
Thus, we have:
[tex]\[ \cos x = 1 \quad \text{and} \quad \cos x = -\frac{1}{2}. \][/tex]
4. Find the corresponding [tex]\(x\)[/tex]-values within the interval [tex]\([0, 2\pi)\)[/tex]:
- For [tex]\(\cos x = 1\)[/tex]:
[tex]\[ x = 0. \][/tex]
- For [tex]\(\cos x = -\frac{1}{2}\)[/tex]:
[tex]\[ x = \frac{2\pi}{3}, \quad \text{and} \quad x = \frac{4\pi}{3}. \][/tex]
5. Gather all the solutions:
Thus, the solutions to the equation [tex]\( 2 \sin^2 x = 1 - \cos x \)[/tex] on the interval [tex]\([0, 2\pi)\)[/tex] are:
[tex]\[ x = 0, \frac{2\pi}{3}, \frac{4\pi}{3}. \][/tex]
Hence, the correct answer is:
[tex]\[ \boxed{0, \frac{2\pi}{3}, \frac{4\pi}{3}}. \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.